Evaluasi Kinerja Struktur Rangka Baja Gedung Bertingkat Beraturan Tahan Gempa Berdasarkan SNI 1729 2015 - Appriliya Destiyani; Iskandar Romey Sitompul; Reni Suryanita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Each building have to be designed so that the building is safe from earthquake load. The purpose of the study is to analyze the drift ratio, reaction force and structural performance at steel structures by using Direct Analysis Method (DAM) and Effective Length Method (ELM). the building structure is analyzed for earthquake loads based on the 2010 earthquake map and 2017 earthquake map. In the study, a 10-story building with a length of x 4 m and y 5 m, a ground floor height of 4,5 m and floors 1-10 is 3,5 m. The total building height is 36 m using IWF 478,447.60.60 and IWF beams 406,403.24.26. The structural system uses an open system without bracing. The structural analysis uses SAP2000 software. The results of the analysis for the DAM and ELM methods show that the deviation between levels is by the provisions of RSNI3 1726 201X, which is less than the deviation between permit levels of 0,0692 m for the ground floor and 0,0538 m for floors 1-10. Structural performance using pushover analysis based on FEMA 356, for the DAM and ELM methods results in an IO (Immediate Occupancy) level of performance with a drift value below 0,7%. Structural analysis found that the force in the DAM method was 1,4% smaller than the ELM method. This is because in the DAM method there is an increase in notional load at the nodal point at all levels. Analysis of the force on the 2017 earthquake map is smaller by 9,8% compared to the 2010 earthquake map. This is due to the acceleration value of the response spectrum on the 2017 map for S1 and Ss by 0,299 and 0,236, while for the 2010 earthquake map for S1 and Ss by 0,441 and 0,274.Keywords: Portal structure of Steel, performance, moment, stress ratio, earthquake hazard map 2017, earthquake hazard map 2010